The fight machine [videorecording (DVD)] - Hunt, Andrew Thomas; Davidson, Craig, 1976-; Hovanessian, Greg; Bryk, Dempsey; Bryk, Greg, 1972-; Henstridge, Natasha; Ironside, Michael, 1950-; Davidson, Craig, 1976- (RLJE Films, 2023)
Two young men from different backgrounds find their destinies linked when they meet up in the world of illegal bare-knuckle fighting.